The The Regulatory Framework of Continuous Teacher Training in the Province of Buenos Aires: Narratives of Teacher Training in the Centers for Training, Information, and Educational Research (CIIE) between 2005 and 2015 (Praxis Educativa, 2025)
The province of Buenos Aires has Centers for Training, Information, and Educational Research (CIIE), responsible for promoting, coordinating, and articulating continuous training actions throughout the provincial territory. Since 2005, with the appointment of new authorities in the Directorate of Continuous Training, a series of policies have been implemented towards the CIIE, leading to a regulatory framework that remains in place today and makes the CIIE a unique system at the national level.In this article, we analyze the regulatory framework of the CIIE built during the period 2005-2015, through the voices of those who led its management at both the provincial and local levels in General Pueyrredon. Decentralization emerges as a key characteristic of the regulatory framework for continuous teacher training in the province, based on the distribution of the CIIE across districts while maintaining centralized leadership in training guidelines and regulatory provisions for their operation. Within this framework, notable aspects include the structure of the CIIE workforce, access to positions through teaching competitions, the reorganization of conditions for external training offers, and the alignment with district needs.
Keywords: Educational policies; continuous teacher training; regulations; CIIE; narratives